Building a Culture of Work Ethic: The Influence of Leadership, Discipline, and the Work Environment in Indonesian Senior High Schools : Penelitian - Lidyawati Tandi Payung; Warman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The culture of work ethic in the educational environment, especially in high school, plays an important role in shaping the character, responsibility, and productivity of school residents. However, there are still many high schools in Indonesia that face challenges in fostering strong and sustainable work ethic values. This study aims to examine in depth the influence of school principal leadership, school community discipline, and work environment on the formation of a work ethic culture. The research uses a qualitative approach through literature studies of scientific sources published from 2020 to 2024. The data were analysed thematically by identifying the relationships between variables through the synthesis of concepts and theories. The results of the study show that the transformational leadership of school principals is very influential in building a commitment to a work ethic. Consistent discipline and a supportive work environment strengthen the application of work values such as integrity, diligence, and responsibility. These findings show that work ethic culture is formed through systemic interactions between leadership style, rule implementation, and work environment conditions. Strategic intervention is needed through leadership training, strengthening the educational discipline system, and improving the quality of school facilities and work climate to realise a work culture with character.